'Pseudofailure' of spinal cord stimulation for neuropathic pain following a new severe noxious stimulus: learning points from a case series of failed spinal cord stimulation for complex regional pain syndrome and failed back surgery syndrome. Issue 2 (May 2016) - Muquit, Samiul; Moussa, Ahmad Abdelhai; Basu, Surajit
Failure of spinal cord stimulation (SCS) may be due to hardware problems, migration of electrodes and, in the long-term, plasticity in the spinal cord with habituation to the stimulation current. We describe a series of seven patients who experienced acute therapeutic loss of SCS effects following an acute nociceptive event unrelated to primary pathology. There were no hardware problems. We called this 'Pseudofailure', as the effective stimulation returned in all patients following a period off stimulation or reprogramming. This phenomenon has not been reported previously in the literature. Over a 4-year period, we managed seven patients with this feature: four had received SCS for complex regional pain syndrome and three for failed back surgery syndrome. In all seven cases, there was cessation of the pain relief afforded by SCS following an acute painful event: four patients had trauma, two patients had domestic electric shock and one patient suffered shingles (varicella zoster infection). We excluded hardware-related problems in all cases. In two patients, SCS effects could be regained by an initial attempt at reprogramming. In the remaining five cases reprogramming was unsuccessful, and stimulation was switched off for several months before recommencing, when we discovered a return of good therapeutic effect. We conclude that SCS may seem to fail following a separate strong nociceptive stimulus. Stimulation may be regained with reprogramming or following a period with stimulation switched off. We would, therefore, advise against removal of SCS hardware in the first instance.